2008 IEEE/AIAA 27th Digital Avionics Systems Conference 2008
DOI: 10.1109/dasc.2008.4702812
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Taxi-out times with a reinforcement learning algorithm

Abstract: Flight delays have a significant impact on the nation's economy. Taxi-out delays in particular constitute a significant portion of the block time of a flight. In the future, it can be expected that accurate predictions of 'wheels-off' time may be used in determining whether an aircraft can meet its allocated slot time, thereby fitting into an en-route traffic flow. Without an accurate taxi-out time prediction for departures, there is no way to effectively manage fuel consumption, emissions, or cost. Dynamicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…11 In addition, reinforcement learning algorithms were developed and investigated to check the accuracy of taxi-out time prediction at several major airports in the United States. [12][13][14] Various regression methods, including multiple linear regression, least median squared linear regression, support vector regression, model trees, and fuzzy rule-based systems, were also applied to several airports in Europe for taxi time prediction problems. 15,16 Each machine learning method was independently applied to the limited test data at different airports under different conditions, and therefore the prediction performance varied with the prediction model.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition, reinforcement learning algorithms were developed and investigated to check the accuracy of taxi-out time prediction at several major airports in the United States. [12][13][14] Various regression methods, including multiple linear regression, least median squared linear regression, support vector regression, model trees, and fuzzy rule-based systems, were also applied to several airports in Europe for taxi time prediction problems. 15,16 Each machine learning method was independently applied to the limited test data at different airports under different conditions, and therefore the prediction performance varied with the prediction model.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of Collaborative Decision Making (CDM) systems at airports within the last few years, practitioners at airports realised the need for having more accurate taxi times and, driven by that, more researchers have analysed the problem of taxi time prediction. Several authors have published their results about taxi-out time prediction at US airports [7,8,9,10,11,12]. Balakrishna et al [7,8,9, 11] used a reinforcement learning algorithm which showed good results for data from Detroit International Airport (DTW) and Tampa International Airport (TPA), but the results were not very consistent for data from John F. Kennedy International Airport (JFK).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have published their results about taxi-out time prediction at US airports [7,8,9,10,11,12]. Balakrishna et al [7,8,9, 11] used a reinforcement learning algorithm which showed good results for data from Detroit International Airport (DTW) and Tampa International Airport (TPA), but the results were not very consistent for data from John F. Kennedy International Airport (JFK). However, this approach cannot provide the same insights into the problem as some other approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Value prediction problems arise in a number of ways: Estimating the probability of some future event, the expected time until some event occurs, or the (action-)value function underlying some policy in an MDP are all value prediction problems. Specific applications are estimating the failure probability of a large power grid (Frank et al, 2008) or estimating taxi-out times of flights on busy airports (Balakrishna et al, 2008), just to mention two of the many possibilities.…”
Section: Value Prediction Problemsmentioning
confidence: 99%